Regularity Relations Signals According Pillars Expressive Between the Narrator and Narrative Discourse Alcinmatugrave Legend Movie In 1900 A Model (Al-Academy, 2017)
This study is concerned with the concept of offering a point of view as a narrative construction element, especially the element and point of view of the novel to the letter Alcinmatugrave both business taken from masterpieces and literary works in the foundation or set of cinema. On the whole, the narrator participate in mock narrative process and support the narrator visual image, especially stories that need to exist scenes prove added to the image that uses signs of reality to take those marks a new dimension not only across the image, but also the intervention of the narrator in the re-formation of this realism marks surrounding Palms perceived and visible and put markers regularly between what the narrative of privacy and image, for this, we find that this research may be unique in the analysis of film "The legend in 1900" to achieve the goals